If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3y + 3z + -8) = 0 Reorder the terms: -1(-8 + 3y + 3z) = 0 (-8 * -1 + 3y * -1 + 3z * -1) = 0 (8 + -3y + -3z) = 0 Solving 8 + -3y + -3z = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -3y + -8 + -3z = 0 + -8 Reorder the terms: 8 + -8 + -3y + -3z = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -3y + -3z = 0 + -8 -3y + -3z = 0 + -8 Combine like terms: 0 + -8 = -8 -3y + -3z = -8 Add '3z' to each side of the equation. -3y + -3z + 3z = -8 + 3z Combine like terms: -3z + 3z = 0 -3y + 0 = -8 + 3z -3y = -8 + 3z Divide each side by '-3'. y = 2.666666667 + -1z Simplifying y = 2.666666667 + -1z
| 4(5x-2)+6=38 | | Cot(cos^-1(7x/8)) | | -3x^2+56x+29=0 | | 2x=5x-90 | | 15x+4=-2x+21 | | 3k^4+10k^3-48k^2=0 | | -3x^2+56t+29=0 | | (3w)w=300 | | 1/18=9.5/x | | 9-(2x-1)=45 | | 8x+4=4x+(-4) | | -5x+3.2=-3.2x+3.6 | | W/2=71 | | f(x)=(x+4)-25 | | 4x/9-7=1 | | .75(h+6)=15 | | 4x-2X+x+59= | | 12(z+2)-4(z-4)=3(z-1)+4(z-3) | | 10-d=-34+5d | | 5(n+8)=n+28 | | 8y+5/4=9y+1/4 | | -6x+3x=8-2x+4+16 | | x+y+x+y+2x+2z= | | 7x+2.0=-4x-5.3 | | 6(4x-9)-7=6(x-3)+65 | | 2x^2+24-60=0 | | 15x+20=20x-5 | | 6(4x-9)-7=6(x-3) | | x^2+6x+-55=0 | | .5(2x-2)=5x+4 | | f(x)=(x+6)-49 | | 48y^2-13y=0 |